Case Report: Late diagnosis of McCune-Albright with severe kyphoscoliosis, acromegaly and tertiary hyperparathyroidism - Bogusławska, Anna; Komisarz-Calik, Maria; Hubalewska-Dydejczyk, Alicja; Korbonits, Márta; Romanet, Pauline; Barlier, Anne; Gilis-Januszewska, Aleksandra (Frontiers in Endocrinology, 2025)
McCune–Albright syndrome (MAS) is a rare genetic disorder caused by somatic activating variants of the GNAS gene. Due to the mosaic state of the variants, the clinical presentation of MAS varies widely depending on the tissues involved. We present a case of a 40-year-old woman who was admitted to the Pulmonary Unit due to progressive pulmonary insufficiency secondary to severe scoliosis. Upon physical examination, hyperpigmented skin lesions on the neck, features of acromegaly, and scoliosis were noted. Radiographic imaging revealed osteolytic lesions of the axial skeleton, which were suspected to be metastases. Imaging via 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) did not confirm metastases and revealed a pituitary lesion. The laboratory workup confirmed acromegaly. Additionally, hypercalcemia, normophosphatemia, elevated parathyroid hormone level, and decreased urine calcium excretion were found. Further examinations revealed kidney stones, cholecystolithiasis, and severe osteoporosis. During follow-up visits, hypophosphatemia has been observed. Bone scintigraphy revealed increased tracer uptake in multiple skeletal system parts, corresponding to degenerative changes. Genetic testing using Sanger sequencing was negative for MEN1 and CDKN1B mutations but revealed a common germline, heterozygous GNAS variant NM_000516.7:c.531-13_531-10del (rs576071932) – classified as a variant of uncertain significance (RCV000597562.1) with a minor allele frequency of 0.265%. Digital Droplet Polymerase Chain Reaction in the circulating cell-free DNA was negative for R201C and R201H GNAS mutation. This case emphasizes that acromegaly, skeletal deformity, hyperpigmented skin lesions, and hyperfunction of the thyroid and parathyroid glands may lead to suspicion of MAS. The diagnosis is often made clinically based on two or more characteristic symptoms. Genetic confirmation of MAS can be challenging.